Histopathology - An Update 2018
DOI: 10.5772/intechopen.76670
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology in Zebrafish (Danio rerio) to Evaluate the Toxicity of Medicine: An Anti-Inflammatory Phytomedicine with Janaguba Milk (Himatanthus drasticus Plumel)

Abstract: The zebrafish Danio rerio appears to be as an alternative experimental model mainly used on toxicological evaluations since the 1990s. In this chapter, we illustrate using a histopathological study the evaluation of a complex phytopreparation with janaguba milk (TPJM, used in popular medicine), which was administrated in zebrafish by immersion in water. We determined (1) lethal concentration 50 (LC 50)-1188.54 μg/mL; (2) the behavioral changes; and (3) the acute administration of TPJM modifications (48 h) at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Worldwide, researches are performed continuously to improve our understanding of how diseases work and how we can treat them. In this context, zebrafish ( Danio rerio ) is a remarkable model organism, particularly for assessment of acute [ 15 ] and reproductive [ 16 – 18 ] toxicity of compounds, either natural [ 19 , 20 ] or synthetic [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, researches are performed continuously to improve our understanding of how diseases work and how we can treat them. In this context, zebrafish ( Danio rerio ) is a remarkable model organism, particularly for assessment of acute [ 15 ] and reproductive [ 16 – 18 ] toxicity of compounds, either natural [ 19 , 20 ] or synthetic [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality was evident in all animals treatmed with EHFAo. In a study by Santos et al [23], it has been observed that, as the concentration of potentially toxic substances in the water increases, the mortality of animals increases. The calculated oral LD 50 was 148.424 mg/kg, which is lower than that calculated for rats in a study by Nomura et al [42].…”
Section: Discussionmentioning
confidence: 99%
“…The search for new therapies that may help in the treatment of various diseases has grown, and zebrafish is used as a model organism for the evaluation of the toxicity of substances of natural and synthetic origin [23].…”
Section: Introductionmentioning
confidence: 99%
“…The latex of mangabeira is often consumed mixed with water to treat inflammatory diseases and other conditions; despite the latex’s frequent usage, studies in the literature about its potential are still lacking compared to the other three parts [ 14 ]. The drug discovery process also relies on the safety of compounds assessed, and zebrafish have been extensively used for this purpose [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish have been shown to be a powerful tool for drug discovery [ 31 , 32 , 33 , 34 , 35 ]. Among their advantages are the low amount of drugs used, low maintenance costs, shorter test periods, easy control of experimental conditions, and the conserved genetic similarity between zebrafish and humans (approximately 70%) [ 15 , 36 ]. The zebrafish pancreas has the same functions as the mammal pancreas concerning glucose homeostasis, including the production and secretion of insulin, glucagon, somatostatin, and digestive enzymes such as amylase [ 37 ].…”
Section: Introductionmentioning
confidence: 99%